Navigating temper tantrums in restrictive mediation: Insight from practitioners - Pratiwi, Hardiyanti; Koenarso, Dyah Ageng Pramesty; Yarliani3, Ikta (Insight: Jurnal Ilmiah Psikologi, 2023)
This research employs a qualitative phenomenological approach to investigate the occurrence of tantrums in early childhood as a result of restrictive media mediation. The study involved 24 lecturers who had children aged 2-6 years exhibiting tantrums. Expressions of tantrums included crying, screaming, throwing objects, holding one's breath, kicking and hitting, rolling, and shouting. Lack of communication before taking away the smartphone when the child is tired, suddenly removing the smartphone when the child is engrossed in using it, and drowsiness serve as triggers for tantrums. Initial parental reactions ranged from confusion to ensuring a safe environment around the child. These responses sometimes involved coercion or physical punishment. Dealing with tantrums proved to be the primary factor influencing parental self-confidence. Weekly tantrums typically lasted for 3–10 minutes and could extend to 8–10 minutes with cooling-down periods. Strategies for handling tantrums included diverting attention, creating a secure environment, meeting the child's needs, ignoring certain behaviors, enforcing consistent rules, providing comfort, and managing one's emotions. Support from family members, behavior management of children, varied distraction activities, open communication, and external support were contributing factors in managing tantrums. Authoritarian parenting patterns, negative peer influences, emotional instability in children, busy parents, poor digital behavior, and financial constraints were inhibiting factors. This study underscores the complexity of addressing tantrums in a context of restrictive media mediation and emphasizes the importance of implementing effective coping mechanisms, enforcing consistent digital discipline, fostering active parent-child communication, and building strong support systems in parenting.